Kinetic studies on clavulanic acid degradation - Bersanetti, P. A.; Almeida, RMRG; Barboza, M.; Araujo, MLG; Hokka, C. O. (Elsevier B.V., 2005)
Clavulanic acid (CA), a potent beta-lactamase inhibitor, is very sensitive to pH and temperature. It is produced by Streptomyces clavuligerus and to optimize both the fermentation step and the downstream process, the expression of the hydrolysis kinetics has to be determined. In the present work the CA degradation rate from various sources was investigated at temperatures of 10, 20, 25, 30 and 40degreesC and PH values of 6.2 and 7.0. The results showed that first-order kinetics explained very well the hydrolysis kinetics and the Arrhenius equation could be applied to establish a relationship between the degradation rate constant and temperature, at both pHs. It has been observed that CA from fermentation medium was much more unstable than that from standard solution and from a commercially available medicine. Also, it was observed that CA was more stable at PH 6.2 than at pH 7.0, irrespective of the CA source. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: antibiotic; clavulanic acid; fermentation; downstream processing; degradation; kinetic parameters